Práticas de letramento na EJA: possibilidades de desenvolvimento da escrita letrada numa interface do oral com o escrito - Santos, Rubeny Ramalho (2014)
Based upon a theoretical-discursive perspective of the speech-writing continuum, the present paper results from a research accomplished with students of the Young and Adult People’s Education programme, the perceptive teaching practice analysis of which pointed out to the need of a methodological intervention as regards the development of the capacity in the production of written texts by students characterized with relative developed competence, in the production of oral texts. To do so, we searched for contribution in papers with wording practices, contemplating the textual genders and the use of didactic sequences as methodological resource, as well. While approaching textual gender works, we opted for the experienced life report gender to accredit the existence of a larger and better gender similarity with the students’ knowledge and their life histories. To accomplish our target, we developed a didactic sequence to contemplate a series of systematically organised activities about the gender we chose to develop the study. Out of this practice, there resulted a group of texts classified as follows: text 01 (initial written production), text 02 (initial oral production), text 03 (final written production), used as basic instruments of the analysis and evaluation of the learning results. For the evaluating analysis, we established a compositional structure of the experienced life report gender as a delimiting parameter of an adequate production. We observed the occurrence of a relative evolution in the students’ knowledge during the accomplishment of the analysis between the initial production context and the final production one. Another point observed in the second moment of the analysis, i. e., the one regarding the texts produced in the oral version, was that we can confirm the students’ better performance in the oral texts. And, in a more comprehensive scope of the analysis, the results showed the development of a more significant learning when we consider the relationships of the interface composing the space between the oral practice and writing as a guiding point to the students’ formation, so confirming the growth of the autonomy and the consequent proficiency in the production of written texts.